Socioéconomie de la monnaie mobile et des monnaies locales au Kenya : quelles innovations monétaires pour quel développement ? - Tristan Dissaux (Revue de la Régulation)
Monetary innovations, giving money new forms and characteristics, are now used to promote the process of economic development. In Kenya, they unfold in mobile money systems such as M-Pesa, as well as in several local currencies implemented on the model of the Bangla-Pesa. These monies have different natures and logics, and the thesis aims to show their impacts and implications. For this, we use data from two field surveys.Monetary innovations challenge development theories, which have largely excluded money from their analyzes, and which generally consider it to be neutral. The study of these schemes allow us to lay the foundations of a monetary theory of development. By doing so, we question the meaning of the concept of development, and the roles that money and finance have to play for it.